Multikriteria Analisis untuk Pengembangan Berkelanjutan Organisasi Pembelajaran - Muhammad Anggung Manumanoso Prasetyo; Agus Salim Salabi (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2022)
Abstract Sustainable issues are complex and intertwined with aspects of education, necessitating the development of design processes that promote innovation and learning. The learner organization is one of educational institutions' governance innovations that reflects adaptive roles in the face of change challenges. The study's goal is to develop the concept of a learner organization (learning organization) into a sustainable learner organization. Top management has the ability to greatly influence management innovation due to its prominent role in the organization. The purpose of this study is to examine the five fundamental dimensions of a learning organization (LO) in the context of educational sustainability. Qualitative research employing grounded method techniques. According to research, the following characteristics of educational organizations are related to learner organizations: (1) learning leadership caderization systems; (2) creation of learning structures; (3) model of holocracy work; (4) formation of individual behavior in the presence of learning opportunities; and (5) learning culture in the context of school organization. Keywords: Learning Organization; Organizational Innovation; Educational Institution Sustainability;